Effect of the pre-treatment and the drying process on the phenolic composition of raisins produced with a seedless Brazilian grape cultivar - Olivati, Carolina [UNESP]; de Oliveira Nishiyama, Yara Paula [UNESP]; de Souza, Reginaldo Teodoro; Janzantti, Natália Soares [UNESP]; Mauro, Maria Aparecida [UNESP]; Gomes, Eleni [UNESP]; Hermosín-Gutiérrez, Isidro; da Silva, Roberto [UNESP]; Lago-Vanzela, Ellen Silva [UNESP] (Elsevier, 2018)
The grape is an important fruit regarding economic and health benefit parameters, because of its large consumption around the world and their bioactive phenolic compounds. The drying process of BRS Morena grapes, whether pre-treated or not with olive oil for producing raisins, resulted in qualitative and quantitative changes in their phenolic composition (anthocyanins, flavonols, stilbenes, hydroxycinammic acid derivatives, flavan-3-ols and proanthocyanidins). The raisins with the pre-treatment preserved more anthocyanins and proanthocyanidins than the raisins not pre-treated. Moreover, the total dehydration time accelerated by approximately 40% in the raisins pre-treated. Therefore, the production of raisins of BRS Morena grapes pre-treated with olive oil as a natural surfactant constitutes an interesting process from both the industrial and health points of view, because of the remarkable reduction in the processing time and the preservation of high concentrations of flavonoids, which have important claims to health benefits from biological activities.
Keywords: (+)-catechin (PubChem CID: 9064); Anthocyanins; BRS Morena; Drying; Flavonoids; GRP, 2-S-glutationil-trans-caftaric (PubChem CID: 71308212); HPLC-DAD-ESI-MSn; malvidin 3-glucoside (PubChem CID: 443652); myricetin 3-glucoside (PubChem CID: 44259426); Phenolic composition; Proanthocyanidins; procyanidin B1(PubChem CID: 11250133); quercetin 3-glucuronide (PubChem CID: 11655911); Raisins; trans-caftaric acid (PubChem CID: 6440397); trans-piceid (PubChem CID: 5281718); vitisin A (PubChem CID: 16131430); vitisin B (PubChem CID: 16138152)